2021
DOI: 10.1093/rheumatology/keab834
|View full text |Cite
|
Sign up to set email alerts
|

mTOR activation in CD8+ cells contributes to disease activity of rheumatoid arthritis and increases therapeutic response to TNF inhibitors

Abstract: Objective This study aimed to understand the role of mTOR in CD8+ cells in the pathogenicity of rheumatoid arthritis (RA) and the changes after treatment with biologic drugs. Methods Peripheral blood mononuclear cells (PBMCs) were isolated from 17 healthy controls and 86 patients with RA. Phosphorylation of mTOR (p-mTOR) and its clinical relevance were evaluated. The role of mTOR in CD8+ cells was also examined in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…CD8 + T cells in RA patients are known to have activated mTOR [ 42 ]. The DEGs that are mapped to the mTOR signalling pathway are shown in Figure 13 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CD8 + T cells in RA patients are known to have activated mTOR [ 42 ]. The DEGs that are mapped to the mTOR signalling pathway are shown in Figure 13 .…”
Section: Resultsmentioning
confidence: 99%
“…The effect of mTOR signalling on glycolysis is mediated by HIF1A and MYC upregulation [ 27 ]. The activation of mTOR was demonstrated in the CD8 + T cells of RA patients [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the levels of the phosphorylated (p) form of mTOR resulted higher in RA CD8 + cells compared to healthy CD8 + cells. Furthermore, p-mTOR levels positively correlate with disease activity and, following in-vitro stimulation, these cells were able to produce granzyme B, granulysin, TNF-α and IFN in parallel to the decrease production of granzyme K. Interestingly, following treatment with TNF-α inhibitors, the levels of p-mTOR levels decreased, suggesting that mTOR activation could be a potential therapeutic target in RA (51).…”
Section: New Findings In Adaptative Immunitymentioning
confidence: 96%
“…The mechanistic target of rapamycin (mTOR) signaling pathway regulates many cellular processes including cell metabolism, migration, differentiation and cytokine responses (22,23). The mTOR signaling pathway is implicated in several inflammatory diseases (23)(24)(25)(26)(27) and rapamycin, an inhibitor of mTOR Complex 1 (mTORC1), can suppress eosinophil differentiation in both allergic and non-allergic airway inflammation (28)(29)(30). Zhang et al reported that eosinophil infiltration in mouse lung was impaired after treatment with rapamycin and other mTOR inhibitors in an ovalbumininduced asthma model (31).…”
Section: Introductionmentioning
confidence: 99%